The average child: Lewis Hine, statistics, and 'social photography'. Issue 3 (3rd July 2018) - Quick, Kathy
Abstract : This project looks at the statistical turn in American sociology in the early twentieth century and its impact on Lewis Hine's 'social photography.' Photographic studies of today are digital and often participatory, yet, their roots can be traced back to Hine's work. The rise of statistical methods in the social sciences coincides with Hine's development as a documentary photographer. Hine is often discussed alongside just one or two of his iconic images. This approach overstates the importance of the single, select print, subverting the essence of Hine's statistical method. The conventional monographic approach is far too limiting for a photographer who produced thousands of images. In 1907, Hine enrolled in Columbia University to study sociology with Professor Franklin Giddings, who was responsible for establishing their leadership position in statistical methods. Hine's longstanding affiliation with Columbia played an important role in shaping his sociological perspective. Hine never thought of his work in terms of individual photographs. What was central to his picture making was a belief in the veracity of a statistical norm. My project examines how the Columbia School provided Hine with the elements upon which his term 'social photography' found meaning and informed how a sociological philosophy might be manifest in photography.